Epidemiology of patients presenting with dyspnea to emergency departments in Europe and the Asia-Pacific region. (October 2019) - Laribi, Said; Keijzers, Gerben; van Meer, Oene; Klim, Sharon; Motiejunaite, Justina; Kuan, Win Sen; Body, Richard; Jones, Peter; Karamercan, Mehmet; Craig, Simon; Harjola, Veli-Pekka; Holdgate, Anna; et al.
Abstract : Objective: The primary objective of this study was to describe the epidemiology and management of dyspneic patients presenting to emergency departments (EDs) in an international patient population. Our secondary objective was to compare the EURODEM and AANZDEM patient populations. Patients and methods: An observational prospective cohort study was carried out in Europe and the Asia-Pacific region. The study included consecutive patients presenting to EDs with dyspnea as the main complaint. Data were collected on demographics, comorbidities, chronic treatment, clinical signs and investigations, treatment in the ED, diagnosis, and disposition from ED. Results: A total of 5569 patients were included in the study. The most common ED diagnoses were lower respiratory tract infection (LRTI) (24.9%), heart failure (HF) (17.3%), chronic obstructive pulmonary disease (COPD) exacerbation (15.8%), and asthma (10.5%) in the overall population. There were more LRTI, HF, and COPD exacerbations in the EURODEM population, whereas asthma was more frequent in the AANZDEM population. ICU admission rates were 5.5%. ED mortality was 0.6%. The overall in-hospital mortality was 5.0%. In-hospital mortality rates were 8.7% for LRTI, 7.6% for HF, and 5.6% for COPD patients. Conclusion: Dyspnea as a symptom in the ED has high ward and ICU admission rates. A variety of causes of dyspnea were observed in this study, with chronic diseases accounting for a major proportion. Abstract : Supplemental Digital Content is available in the text.